Hubungan Sanitasi Pasar Dengan Kepadatan Lalat Pada Pasar Induk Minasa Maupa Kabupaten Gowa - Muh.Ikbal; Sarmaliana (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2023)
The market is one of the favorite places for flies to grow and breed because in fact the market produces a lot of wet waste, organic waste, from activities where fish, meat and vegetables are sold, as well as TPS and waste disposal channels which are the cause of the presence of flies in the market resulting in overcrowding. The research objective was to determine the relationship between market sanitation and fly density at the Minasa Maupa Main Market, Gowa Regency. This type of research is Analytical Observational with a cross sectional approach, the sampling technique used is non-probability (purposive sampling) the number of samples is 70 and analyzed using the chi square test.The results showed that there was a relationship between landfills and the density of flies p = 0.021 < α = 0.05 and x2hit 5.348 > x2hit 3.841, there was a relationship between sewers and fly density levels p = 0.002 < α = 0.05 and x2hit 9.219 > x2hit 3,841, there is a relationship between food vendors and the density of flies p = 0,001 > α= 0,05 and x2hit 13.676 > x2hit 3,841, there is no relationship between clean water shipping and the level of the navy p= 0,111 < α= 0 ,05 and x2hit 2.541 < x2hit 3.841.The conclusion of this study is that there is a relationship between landfills, sewerage, and food vendors with fly density and there is no relationship between the provision of clean water and fly density. It is hoped that the market manager will provide trash cans for traders, provide clean water and also maintain market cleanliness and fly control efforts. Keywords: Flies, Market, SPAL, Garbage disposal, Clean water